Shopping mall as new urban core? A morphological study of contemporary urban fabric influenced by shopping malls - Lontoc, Don Johnson; Arellano, Abigail; Baquiran, Raquel (Journal of Architecture and Urbanism, 2023)
A major transformation in contemporary cities is the evolution of the urban core. This paper investigated the issues associated with the surge of shopping malls as an alternative public space and how they may be classified as an “urban core” of contemporary cities. This paper aimed to interpret a new form of urban core and its set of spatial indicators relative to its socio-spatial network with its surroundings. This paper also aimed to introduce spatial indicators of urban core for the practical use of institutional units on how to create equally attractive public place alternatives to shopping malls. The paper argued that shopping malls with significant floor areas, accumulated over the years, substantially influence their surrounding area by increasing lot density and linkages. While these shopping mall complexes do not meet the threshold population to be considered “urban core”, the case studies have demonstrated that shopping malls can establish social hubs that centralize urban activities, and construct a “place” or “destination” with congregated urban services such as public plazas and public transport network.